Pembudayaan Literasi Kritis: Cultivation of Critical Literacy - Rahman, Yurni; Atjalau, Cutri (Universitas Muhammadiyah Sidoarjo, 2019)
This research has a long-term goal, namely how to apply the culture of critical literacy in the face of globalization so that students are able to compete at the national level and even at the global level. This research method is an explanatory research process. Information about Literacy Management in the face of globalization. Can conclude that students only read interest in 1-2 times each week. This requires special attention from teachers and parents in encouraging children / students to be more interested in reading at least reading textbooks taught in school. When it is considered normal, then the child will never be able to point to other good things, and the knowledge he has will be very narrow, whereas when children want to do literacy critically, then their thinking will be broad, sociable, sociable and be responsive to what happens.